OpenGL game development by example : design and code your own 2D and 3D games efficiently using OpenGL and C++ - Madsen, Robert; Madsen, Stephen (Community experience distilled., 2016)
Design and code your own 2D and 3D games efficiently using OpenGL and C++About This Book Create 2D and 3D games completely, through a series of end-to-end game projects Learn to render high performance 2D and 3D graphics using OpenGL Implement a rudimentary game engine using step-by-step codeWho This Book Is ForIf you are a prospective game developer with some experience using C++, then this book is for you. Both prospective and experienced game programmers will find nuggets of wisdom and practical advice as they learn to code two full games using OpenGL, C++, and a host of related tools. What You Will Learn Set up your development environment in Visual Studio using OpenGL Use 2D and 3D coordinate systems Implement an input system to handle the mouse and the keyboard Create a state machine to handle complex changes in the game Load, display, and manipulate both 2D and 3D graphics Implement collision detection and basic physics Discover the key components needed to complete a polished game Handle audio files and implement sound effects and musicIn DetailOpenGL is one of the most popular rendering SDKs used to develop games. OpenGL has been used to create everything from 3D masterpieces running on desktop computers to 2D puzzles running on mobile devices. You will learn to apply both 2D and 3D technologies to bring your game idea to life. There is a lot more to making a game than just drawing pictures and that is where this book is unique! It provides a complete tutorial on designing and coding games from the setup of the development environment to final credits screen, through the creation of a 2D and 3D game. The book starts off by showing you how to set up a development environment using Visual Studio, and create a code framework for your game. It then walks you through creation of two gamesa 2D platform game called Roboracer 2D and a 3D first-person space shooter gameusing OpenGL to render both 2D and 3D graphics using a 2D coordinate system. You'll create sprite classes, render sprites and animation, and navigate and control the characters. You will also learn how to implement input, use audio, and code basic collision and physics systems. From setting up the development environment to creating the final credits screen, the book will take you through the complete journey of creating a game engine that you can extend to create your own games. Style and approachAn easy-to-follow guide full of code examples to illustrate every concept and help you build a 2D and 3D game from scratch, while learning the key tools that surround a typical OpenGL project.